1997
DOI: 10.1210/endo.138.6.5191
|View full text |Cite
|
Sign up to set email alerts
|

Endothelins Stimulate Deoxyribonucleic Acid Synthesis and Cell Proliferation in Rat Adrenal Zona Glomerulosa, Acting through an Endothelin A Receptor Coupled with Protein Kinase C- and Tyrosine Kinase-Dependent Signaling Pathways

Abstract: The effects of endothelins (ET) on the proliferative activity of the rat adrenal cortex have been investigated in vivo, using an in situ perfusion technique of the intact left gland. The chemicals were dissolved in the perfusion medium, and the perfusion continued for 120 min. ET-1 concentration dependently increased the mitotic index and [3H]thymidine incorporation into DNA in the zona glomerulosa (ZG; 6- and 3-fold increases, respectively, at a 10(-8) M concentration), but not in the inner adrenocortical lay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
30
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 40 publications
(30 reference statements)
0
30
0
Order By: Relevance
“…The synthesis of all the components of the ET system in the zona glomerulosa, the proliferative layer involved in the growth of the entire adrenal cortex, suggests that the ET system is involved in this biological effect. This was recently demonstrated by Mazzochi et al (1997), who found that ETs stimulate the proliferation of rat adrenal zona glomerulosa cells via ET-A receptors. The use of a sensitive, specific RNA probe and a specific polyclonal antibody made it possible to map in detail the cellular distribution of ECE-1 mRNA and protein in the cells of a variety of human tissues.…”
Section: Discussionmentioning
confidence: 62%
“…The synthesis of all the components of the ET system in the zona glomerulosa, the proliferative layer involved in the growth of the entire adrenal cortex, suggests that the ET system is involved in this biological effect. This was recently demonstrated by Mazzochi et al (1997), who found that ETs stimulate the proliferation of rat adrenal zona glomerulosa cells via ET-A receptors. The use of a sensitive, specific RNA probe and a specific polyclonal antibody made it possible to map in detail the cellular distribution of ECE-1 mRNA and protein in the cells of a variety of human tissues.…”
Section: Discussionmentioning
confidence: 62%
“…14 ET-1 acts as secretagogue for calf adrenal zona glomerulosa cells 25 and is trophic for rat adrenal zona glomerulosa cells. 26 These authors suggested that ET-1 could be the factor that causes enhanced aldosterone secretion in APAs. The decrease in ET B receptors reported by Rossi et al 27 and Zeng et al 17 could cause the higher plasma ET-1 concentrations described by some, 16 as ET B may also function as a physiological clearance receptor for extracellular ET-1.…”
Section: Discussionmentioning
confidence: 99%
“…ET family ligands, which include endothelin-1 (ET-1), vasoactive intestinal contractor (VIC)/endothelin-2 (ET-2), and endothelin-3 (ET-3), are peptides composed of 21 amino acid residues. These isopeptides have a variety of biological roles, including involvement in vasoconstriction (Yanagisawa et al 1988), bronchial smooth muscle contraction (Mckay et al 1991), and cell growth (Lahav et al 1996, Mazzocchi et al 1997. The effects of these peptides are mediated by receptors (ETRs) that are classified into two subtypes, the endothelin A receptor (ETA) and the endothelin B receptor (ETB).…”
Section: Introductionmentioning
confidence: 99%